Let's fill in the blanks step by step, starting with the expression:
\[ (13/4 x - y/7 - 23) - (3/7 y - x/4 + 10) \]
-
Distributing the negative sign: \[ 13/4 x - y/7 - 23 - 3/7 y + x/4 - 10 \]
-
Combine like terms for the \(x\)-terms:
- We have \(13/4 x + x/4\).
- To add these, we need a common denominator. The common denominator of 4 is 4: \[ 13/4 x + 1/4 x = (13/4 + 1/4)x = (14/4)x = \frac{7}{2}x \]
So, for the \(x\)-terms: \[ 13/4 x + x/4 = \frac{7}{2}x \]
- Combine the \(y\)-terms:
- We have \(-y/7 - 3/7 y\).
- Combining these gives: \[ -y/7 - 3/7 y = -1/7 y - 3/7 y = -\frac{4}{7}y \]
So, for the \(y\)-terms: \[ -y/7 - 3/7 y = -\frac{4}{7} y \]
- Combine the constants:
- We have \(-23 - 10\).
- This gives: \[ -23 - 10 = -33 \]
So, for the constants: \[ -23 - 10 = -33 \]
Putting it all together, we have:
\[ \frac{7}{2} x - \frac{4}{7} y - 33 \]
Thus, filling in the blanks, the final expression is:
The expression \( \frac{7}{2}x - \frac{4}{7}y - 33 \) represents the difference.